Nutrient Uptake, Tuber Yield and Soil Physicochemical Properties as Influenced by Tillage and Nutrition for Tannia (Xanthosoma sagittifolium (L.) Schott) in the Red Soils of Southern Kerala - OK, Swadija; Jayapal, Atul; Vijayaraghavakumar (JOURNAL OF ROOT CROPS, 2022)
A study was undertaken at College of Agriculture, Vellayani, Thiruvananthapuram, Kerala during 2014- 2016 to identify an ideal tillage system and plant nutrition for tannia for improving the nutrient uptake and tuber yield of tannia and also to evaluate their effects on the physico-chemical properties of soil. The design used was split plot and was replicated four times. The main plot treatments were conventional tillage followed by pit system, conventional tillage followed by mound system, deep tillage followed by pit system and deep tillage followed by mound system. The sub plot treatments were combinations of soil conditioners (control, coir pith, rice husk) and nutrient management systems (integrated nutrient management (INM) and organic nutrition). The results revealed that deep tillage to a depth of 30 cm followed by pit or mound system of planting, application of coir pith as soil conditioner (@ 500 g plant-1) and organic nutrition (FYM @ 37.5 t ha-1 + wood ash @ 2 t ha-1) is ideal for enhancing nutrient uptake and tuber uptake of tannia without depletion of soil nutrient status